Effects of Insecticides on Sugarcane Termites in Modhupur Tract (Bangladesh Journal of Agricultural Research, 2012)
An experiment was conducted with insecticides, namely Krisban 50WP,   Neptune 48EC, Aincoban 48EC, Greater 48EC, Chlorguard 48EC, Chlorban 40.8EC, Vifos 20EC, Luciban 20EC, Bismark 20SP, Imidagold 20SL, Lorsban 15G to find out their effectiveness for controlling sugarcane termites and on the growth and yield of sugarcane at Sreepur. All these insecticides were applied @ 2.25/0.20 Kg ha-1 or l ha-1 during plantation, April and May. All of them except Aincoban, Chlorgaurd and Bismark provided 71-97% termite population control. Germination of sugarcane bud was higher in chemical treated plot than the untreated control. Yield of cane increased in Greater 48EC, Chlorban 40.8EC, Luciban 20EC, Imidagold 20SL and Lorsban 15G treated plots. DOI: http://dx.doi.org/10.3329/bjar.v37i2.11232 Bangladesh J. Agril. Res. 37(2): 295-299, June 2012